Comparing Conformal and Quantile Regression for Uncertainty Quantification: An Empirical Investigation - Kumar, Bhargava; Kumar, Tejaswini; Nadakuditi, Swapna; Patel, Hitesh; Gupta, Karan (International Journal of Computing and Engineering, 2024)
Purpose: This research assesses the efficacy of conformal regression and standard quantile regression in uncertainty quantification for predictive modeling. Quantile regression estimates various quantiles within the conditional distribution, while conformal regression constructs prediction intervals with guaranteed coverage. Methodology: By training models on multiple quantile pairs and varying error rates, the analysis evaluates each method's performance. Findings: Results indicate consistent trends in coverage and prediction interval lengths, with no significant differences in performance. Quantile regression intervals lengthen toward the distribution tails, while conformal regression intervals lengthen with higher coverage. Unique contribution to theory, policy and practice: On the tested dataset, both methods perform similarly, but further testing is necessary to validate these findings across diverse datasets and conditions, considering computational efficiency and implementation ease to determine the best method for specific applications.